2021
DOI: 10.1073/pnas.2102602118
|View full text |Cite
|
Sign up to set email alerts
|

Anthracene-induced formation of highly twisted metallacycle and its crystal structure and tunable assembly behaviors

Abstract: Polycyclic aromatic hydrocarbons (PAHs) continue to attract increasing interest with respect to their applications as luminescent materials. The ordered structure of the metal−organic complex facilitates the selective integration of PAHs that can be tuned to function cooperatively. Here, a unique highly twisted anthracene-based organoplatinum metallacycle was prepared via coordination-driven self-assembly. Single-crystal X-ray diffraction analysis revealed that the metallacycle was twisted through the cooperat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 57 publications
1
14
0
Order By: Relevance
“…The strict spatial separation enforced by the metal–organic architecture preserved the fluorescence in both high- and low-concentration regimes, allowing white-light emission. Similar principles were recently reported in a metallacycle where a high degree of intramolecular twist constrained the incorporated anthracenes, increasing the emission intensity . Furthermore, the same group, working with the Sun group, showed that metal–organic capsules can self-assemble into soft superstructures of up to the millimeter scale …”
Section: Heteroleptic Assemblies: Incorporation Of Multiple Ligands G...supporting
confidence: 74%
“…The strict spatial separation enforced by the metal–organic architecture preserved the fluorescence in both high- and low-concentration regimes, allowing white-light emission. Similar principles were recently reported in a metallacycle where a high degree of intramolecular twist constrained the incorporated anthracenes, increasing the emission intensity . Furthermore, the same group, working with the Sun group, showed that metal–organic capsules can self-assemble into soft superstructures of up to the millimeter scale …”
Section: Heteroleptic Assemblies: Incorporation Of Multiple Ligands G...supporting
confidence: 74%
“…This hysteresis in 1 H NMR spectra between heating and cooling cycles is in accordance with the hysteresis observed in transmittance spectra (Figure a). For DL-A 20 (Figure b), all the resonances of proton on DL-A 20 maintain the similar peak shape as the temperature increased or decreased (Figure S8), indicating no significant hydration or dehydration of polypeptides because of their random coil structures. , …”
Section: Resultsmentioning
confidence: 88%
“…After heating from 45 to 55 °C, sharper peaks of the protons on the side chains are observed as the temperature increased to 55 °C (Figure S7), indicating the less conformation restriction and faster molecular movements due to deaggregation of polypeptides, and the deaggregation is induced by the hydration of polypeptides at temperature higher than T cp . 47,48 The sharp transition of peak shape when heating from 45 to 55 °C can be attributed to the simultaneous fracture of cooperative hydrogen bonds between chiral polypeptides (Figure 5a). 49 However, when cooling from 55 to 25 °C, the peaks become broader gradually (Figure S7), meaning the blunt re-formation of hydrogen bonds between chiral polypeptides and slow reaggregation of polypeptides.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Self-assembled macrocycles, [1][2][3][4][5][6][7] cages, [8][9][10][11][12][13] and oligomers [14][15][16] featuring palladium-coordination nodes are a mainstay of supramolecular chemistry due to their unique mechanical, [14][15][16][17][18] optoelectronic, [19][20][21][22][23][24][25][26][27][28] and catalytic [29][30][31][32][33][34][35][36][37][38][39][40][41][42] applications. The squareplanar coordination geometry of the coordination node permits the synthesis of well-dened constructs invoking simple geometric design principles.…”
Section: Introductionmentioning
confidence: 99%